Matrix metalloproteinases in peripheral blood and cerebrospinal fluid in patients with Alzheimer's disease - Horstmann, Solveig; Budig, Leila; Gardner, Humphrey; Koziol, James; Deuschle, Michael; Schilling, Claudia; Wagner, Simone (International psychogeriatrics, 2010)
Background: Deposition of amyloid β in senile plaques and in cerebral blood vessels is one hallmark of the pathogenesis of Alzheimer's disease (AD). The ability of several matrix metalloproteinases (MMPs) to degrade amyloid precursor protein leading to aggregation of amyloid β, as well as the increased expression of MMPs in post mortem brain tissue of Alzheimer's patients, indicate that MMPs play an important role in the pathogenesis of AD.Methods: We investigated levels of MMP-2,-3,-9 and -10 in plasma and cerebrospinal fluid (CSF) of AD patients (n = 14) by gelatin and casein zymography. Comparisons between AD patients and controls relative to levels of MMP-2, MMP-3, MMP-9, and MMP-10 were made with Wilcoxon rank statistics. Pearson correlations were computed as measures of association.Results: MMP-3 in AD was significantly elevated in plasma (p = 0.006) and there was a trend towards increase in CSF (p = 0.05). MMP-2 in CSF of AD patients was significantly decreased (p = 0.02) while levels in plasma remained unchanged. MMP-9 and MMP-10 could not be detected in CSF; MMP-10 was unchanged in plasma, but MMP-9 was significantly decreased (p = 0.02).Conclusions: These findings constitute further evidence for the important role of MMPs in the pathogenesis of AD.
Gesehen am 21.04.2023